Analytical Study of The Methods of Parental Treatment and Its Relationship With Aggressive Behavior Among Pupils’ Basic Education and its Impact on Human Development - Tayoub, Mahmoud; Abdullah, Etedal; Shmelleis, Afifah (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدفت الدراسة إلى التعرف على طبيعة علاقة أساليب المعاملة الوالدية ، وأثرها على السلوك العدواني للتلاميذ ، وللوقوف على أساليب المعاملة الوالدية في محافظة اللاذقية, أخذنا عينة بلغ حجمها 247 طالباً من مختلف الصفوف الدراسية، وخلصت الدراسة إلى أن المستوى التعليمي للوالدين له تأثيرٌ إيجابيٌ على خفض السلوك العدواني للتلاميذ، وأوضحت الدراسة أيضاً أن هناك علاقة ارتباطية ذات دلالة إحصائية بين المستوى الاقتصادي للأهل وسلوك الأبناء العدواني كما أظهرت الدراسة أن حوالي 27.530% من الأسر يقل دخلها عن 5000 ليرة سورية، كما أوضحت أن مهنة الأب تؤثر على السلوك العدواني للأبناء، وأوضحت أن نسبة 65.344% من الآباء لا يهتمون بمشكلات أولادهم، و 73.198% منهم يضربون أولادهم، وتبين لنا أيضاً أن 55.951% من الآباء يعاملون أولادهم بطريقة سيئة، وهذا ينعكس سلباً على سلوك الأبناء العدواني ، كذلك خلصت الدراسة إلى أن 55.923%من الآباء يأخذون رآي الأبناء في أشياءهم الخاصة ،وخلصت الدراسة أيضاً إلى أن المعاملة الوالدية لها تأثيرٌ هامٌ على سلوك الأبناء العدواني . The study aims at cognizing the nature of the relation of methods of parental treatment effects on the aggressive behavior of the students. To observe the methods of parental treatment methods in the province of Lattakia, we take a sample of 247 students from different classes. The result of the study was that the educational level of the parents has a positive effect on decreasing the aggressive behavior. The study shows that about 27.530% of families have less than 5000 s.p income amount, it has also revealed that the fathers’ professions influence their sons .the study has shown that a ratio of 65.344% of parents do not take care of the problems of children and 73.198% of parents beat up their children. Also we concluded that 55.951% of parents badly treated their children, which reflects negatively on the children’s aggressive behavior. The study has found that 55.923% of them take into consideration the opinion of their children about their private affairs. Also we have found that the parental treatment has a significant effect on the children’s aggressive behavior.